Ночь длинных стволов - Уфимцев Руслан Разапович (Русский бестселлер, 2001)
Экземпляры: ф.1 (2007) / Инвентарный номер: 51212 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: У 88 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44